Conceptual Approaches to Robustness Assessment of Building Structures, Buildings and Facilities - Ashot G. Tamrazyan (Железобетонные конструкции)
Some examples of failures of structures, buildings, where the lack of robustness was recognized, are analyzed. Several author’s definitions for robustness are presented and discussed. Special emphasis is given to the fact that define robustness as an intrinsic structural property and the other hand it as a property of the structure and its environment. Some related concepts are presented and discussed.The most important proposed measures for robustness are also present-ed including some illustration examples. Finally, a comparison between them is made and the respective shortcomings are identified. After anal-ysis of the robustness nature, a new structural oriented definition is pro-posed. Based on the highlighted shortcomings of the existing measures, in particular those related with the application to deteriorated structures, a conceptual framework for robustness assessment is proposed.